Estudo In vitro de nanocompósitos para a liberação lenta de nitrogênio sobre a alimentação animal - Cruz, Camila Conceição Tomé da (2016)
Supplementation with nonprotein nitrogen (NPN) has been widely used in ruminant feeding in diets of low quality forages. This is because these animals have a number of microorganisms in the rumen able to use ammonia for microbial protein production of excellent quality, ammonia is obtained through the action of urease enzyme on the nitrogenous products supplied in food, for example, urea. However, an excessive consumption of urea may result in poisoning by NH3. Thus, a controlled release of urea into the rumen is an essential aspect for ruminants feed, but few studies to control the release of urea in the rumen have been identified to date Thus this paper proposes obtaining nanocomposites montmorillonite and urea, formulated by the extrusion process, as a source of slow-release nonprotein nitrogen on the feed. The materials were characterized by diffraction of X-ray (XRD), scanning electron microscopy (SEM), thermal gravimetric analysis (TGA) and elemental analysis (CHN). Also was studied the behavior solubilization in an aqueous medium of urea present in the nanocomposites. Characterization results can be observed that the montmorillonite exfoliation suffered in all nanocomposites, urea served as montmorillonite dispersed phase in a matrix. The release results showed that the presence of MMT acts as a barrier to release of urea making all nanocomposites have slower release of urea compared to the pure material In order to assess the effect of the use of such nanocomposites as non-protein nitrogen supplement for sugarcane (bulky), was carried out in vitro digestibility test for dry matter, which simulates the food digestion conditions in the rumen. Different nanocomposite showed gain on the digestibility of sugar cane, which is considered low quality forage, especially for presenting low protein value and be difficult to digest. The nanocomposite MMT/Ur 1:4/HG 2% was the most effective in increasing the digestibility of the sugar cane. The gain on digestibility was not very significant for displaying nanocomposites release kinetics urea very slowly, suggesting that an ideal release rate is required, being synchronized with the power supply supplied from the carbohydrate in the diet. The pH remained within the optimal range for urease activity, the enzyme responsible for metabolizing urea to ammonia and also for maximum microbial synthesis. These results show that the development of nanostructures is a powerful tool for increasing the efficiency of conventional fodder, and can serve as a basis for further in vivo testing.